Schistosomiasis mansoni: evidence for a milder response in germfree mice - Viera, Leda Q.; Moraes-santos, Tasso (Revista do Instituto de Medicina Tropical de São Paulo, 1987)
Germfree (GF and conventional (CV) mice were infected intraperitoneally with GF cercariae of Schistosoma mansoni and kept for six weeks. Twenty four hours before killing, they were injected with [³H]-thymidine. Schistosoma worms, harvested after perfusion of portal system, were counted as well as eggs from liver and intestines. Liver was also used for DNA, protein, and collagen determinations. [³H] -Thymidine incorporation and collagen determinations were used to establish the indices given by the difference between their contents in infected and control animals and expressed per thousand eggs in liver. The recovery of worms in GF mice was around twice as much as in CV ones, and the total number of eggs was higher in the liver of GF animals. No hypertrophy of liver cells was observed by the ratio protein/DNA, but [³H]-thymidine incorporation into DNA was higher than in controls in both GF and CV infected animals. The [³H]-thymidine and collagen indices were lower in GF animals which indicate a more discrete cellular replication and smaller collagen content in relation to the number of eggs present in livers of these mice. It was concluded that the disease seems to be less severe in GF animals.